Clinical impact of perioperative myocardial infarction after pancreatic surgery - Dovzhanskiy, Dmitriy I.; Hackert, Thilo; Krumm, Jens; Hinz, Ulf; Roggenbach, Jens; Hofer, Stefan; Büchler, Markus W.; Werner, Jens (Journal of gastrointestinal surgery, 2014)
The aim of this study was to evaluate the incidence, clinical impact and outcome of perioperative myocardial infarction (PMI) in patients undergoing pancreatic surgery.